2020
DOI: 10.3390/ijerph17051548
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Climatic and Landscape Risk Factors for Lyme Disease Cases in the Upper Midwest and Northeast United States

Abstract: Lyme disease, recognized as one of the most important vector-borne diseases worldwide, has been increasing in incidence and spatial extend in United States. In the Northeast and Upper Midwest, Lyme disease is transmitted by Ixodes scapularis. Currently, many studies have been conducted to identify factors influencing Lyme disease risk in the Northeast, however, relatively few studies focused on the Upper Midwest. In this study, we explored and compared the climatic and landscape factors that shape the spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…While birds are likely involved in dispersing ticks among locations within New York, there is no evidence that migration of tick-infested birds is driving tick range expansions. Differences in the drivers of ranges expansion within New York, which is not at the current northern boundary of the species range, and into Canada, which is at the species range boundary, should be expected as the processes impacting tick population dynamics are likely to vary among regions with different underlying ecologies and environmental conditions [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…While birds are likely involved in dispersing ticks among locations within New York, there is no evidence that migration of tick-infested birds is driving tick range expansions. Differences in the drivers of ranges expansion within New York, which is not at the current northern boundary of the species range, and into Canada, which is at the species range boundary, should be expected as the processes impacting tick population dynamics are likely to vary among regions with different underlying ecologies and environmental conditions [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study in Canada showed that climate warming with a higher average daily minimum summer temperature was positively associated with tick densities, and suggested that a relatively warm microclimate may even benefit tick populations [13] . A recent study also demonstrated that the climatic variables generally had opposite effects on Lyme cases in the Northeast and Upper Midwest of the USA [5].…”
Section: Introductionmentioning
confidence: 95%
“…Lyme disease has become a serious public health concern and a recent study made a prediction that human Lyme cases in the USA will increase by 20% in the next two decades [4]. Better understanding the spatial pattern of Lyme disease and the driving factors is not only beneficial to its prediction but also contributes to better prevention [5].…”
Section: Introductionmentioning
confidence: 99%
“…Another research study dealt with Lyme disease, which represents one of the most important vector-borne diseases globally [ 20 ]. A steady increase in affected humans has been observed in the United States and no human vaccines are available; therefore, the motivation for the study was to improve the knowledge about the risk factors for Lyme disease infections [ 20 , 21 , 22 ]. In this context, Dong and colleagues (2021) compared the climate and landscape risk factors for Lyme disease in the Upper Midwest and Northeastern regions of the United States, where Lyme disease is endemic and transmitted by Ixodes scapularis (vector: deer ticks).…”
mentioning
confidence: 99%
“…The study analyzed the relationship between the annual number of human Lyme disease cases for each county from 2012 to 2016, and the predictor variables of climate, seven national land cover classes and the distance to the origin areas of Lyme disease. For this purpose, the authors used a generalized linear mixed model with negative binomial regression [ 22 ]. The model results indicated that in both analyzed regions the landscape factors (related to developed areas and forest) had similar effects on the occurrence of Lyme disease.…”
mentioning
confidence: 99%